“Thinking about Thinking as a Department Chair” - Duncan H Spelman; Wiley C Davi (Academic Chairpersons Conference Proceedings, 2015)
Engaging in metacognition (thinking about thinking) can improve one’s effectiveness as a leader and department chair. Participants will be introduced to a model, building on Argyris's "Ladder of Inference," that can guide a metacognition practice.
Keywords: metacognition; biases; emotions; identities; unconscious